Reinterpretasi Ayat-Ayat Polemis Al-Qur'an dalam Jembatan Dialog Antaragama - Firdaus, Muhamad Yoga (Jurnal Penelitian Ilmu Ushuluddin, 2025)
This study aims to analyze the reinterpretation of polemical verses in the Qur'an from the perspective of modern Muslim reformist hermeneutics, particularly through Mun'im Sirry's study in Scriptural Polemics (2014). Using qualitative methods and a literature review approach, this study utilizes the contextual hermeneutics theoretical framework of Fazlur Rahman, Abdullah Saeed, Nasr Hamid Abu Zayd, and Muhammad Arkoun to explore the dynamics of textual meaning between its historical context and universal values. The results show that reformist interpretations of verses such as Q.S. 3:85 and Q.S. 5:51 shift the exclusive meaning towards an inclusive paradigm that emphasizes the ethics of coexistence, religious freedom, and human solidarity. Polemical verses are no longer read as legitimizing theological conflict, but rather as a moral basis for fair and civilized interfaith relations. This study recommends strengthening contextual interpretation studies in Islamic academic circles and integrating pluralistic values into contemporary religious discourse.